Application of similarity theory in modeling the output characteristics of proton exchange membrane fuel cell. (26th October 2021) - Bai, Fan; Lei, Le; Zhang, Zhuo; Li, Hailong; Yan, Jinyue; Chen, Li; Dai, Yan-Jun; Chen, Lei; Tao, Wen-Quan
Abstract: Proton Exchange Membrane Fuel Cell (PEMFC) has attracted widespread interest. In the present work, similarity analysis is adopted for a three-dimensional single-phase isothermal model of PEMFC to derive similarity criteria. Seven kinds of input criteria (Π1  ∼ Π7 ) are obtained, relevant to the fluid flow, pressure drop, flow resistance in a porous medium, activity loss, diffusion mass transfer, convective mass transfer and ohmic loss in PEMFC respectively. Dimensionless voltage and dimensionless current density are defined as two output criteria. Numerical verifications show that if the seven criteria keep their individual values with their components vary in a wide range, the dimensionless polarization curves keep the same with a deviation about 1%, showing the validity and feasibility of the present analysis. From the effect on the dimensionless polarization curve, sensibility analysis shows that the seven criteria can be divided into three categories: strong (Π4 and Π7, -94.9% ∼ +349.2%), mild to minor (Π5 and Π6, -4.5% ∼ +5.0%), and negligible (Π1, Π2 and Π3, -1.2% ∼ +1.1%). The similarity analysis approach can greatly save computation time in modeling the output characteristics of PEMFC. Highlights: Seven criteria composed of PEMFC input parameters are derived. Dimensionless voltage and electrical current are defined and calculated. The correctness and application prospect of the derived criteria are presented. Sensibilities of seven similarity criteria on the polarization curve are analyzed.